2018
DOI: 10.3389/fnins.2018.00504
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin Is Required for β-Amyloid Toxicity in Human iPSC-Derived Neurons

Abstract: Our understanding of the molecular processes underlying Alzheimer’s disease (AD) is still limited, hindering the development of effective treatments, and highlighting the need for human-specific models. Advances in identifying components of the amyloid cascade are progressing, including the role of the protein clusterin in mediating β-amyloid (Aβ) toxicity. Mutations in the clusterin gene (CLU), a major genetic AD risk factor, are known to have important roles in Aβ processing. Here we investigate how CLU medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 53 publications
2
31
0
Order By: Relevance
“…APOE4 GABAergic interneurons experienced degeneration in culture (though glutamatergic and dopaminergic neurons did not), while cholinergic neurons exhibited elevated sensitivity and altered Ca 2+ signaling in response to glutamate toxicity [39,110]. Intriguingly, iPSC-derived excitatory neurons lacking the SAD risk factor CLU were less sensitive to Aβ-induced toxicity, consistent with CLU single nucleotide polymorphisms being associated with reduced AD risk [31,115]. Sullivan and colleagues took a broader approach, performing a shRNA knockdown screen of more than 50 AD candidate genes in iPSC-derived neurons, examining effects on Aβ secretion and tau phosphorylation [116].…”
Section: Human Neural Progenitor Cell and Neuron Modelsmentioning
confidence: 84%
“…APOE4 GABAergic interneurons experienced degeneration in culture (though glutamatergic and dopaminergic neurons did not), while cholinergic neurons exhibited elevated sensitivity and altered Ca 2+ signaling in response to glutamate toxicity [39,110]. Intriguingly, iPSC-derived excitatory neurons lacking the SAD risk factor CLU were less sensitive to Aβ-induced toxicity, consistent with CLU single nucleotide polymorphisms being associated with reduced AD risk [31,115]. Sullivan and colleagues took a broader approach, performing a shRNA knockdown screen of more than 50 AD candidate genes in iPSC-derived neurons, examining effects on Aβ secretion and tau phosphorylation [116].…”
Section: Human Neural Progenitor Cell and Neuron Modelsmentioning
confidence: 84%
“…Common variant stem cell models have generally lagged behind with only a small number of target models developed, most notably APOE 144,145 . Only three loci identified exclusively by GWAS, PICALM 146 , CLU 147…”
Section: Genetic Modelling and Disease Mechanismsmentioning
confidence: 99%
“…In this mouse model, Abeta deposits are found as increased CAA deposits, and overall Abeta load is decreased within the brain ( Wojtas et al, 2017 ). These paradoxical results were corroborated by another group who showed that clusterin expression is required for Abeta toxicity in human induced pluripotent stem cell (iPSC)-derived neurons ( Robbins et al, 2018 ). In agreement, in primary neurons, siRNA silencing of clusterin expression provides protection against Abeta toxicity ( Killick et al, 2014 ).…”
Section: Clusterinmentioning
confidence: 74%
“…In agreement, in primary neurons, siRNA silencing of clusterin expression provides protection against Abeta toxicity ( Killick et al, 2014 ). However, as shown by Robbins et al (2018) , the loss of clusterin expression results in a change in the expression of a variety of genes; thus, it is currently unclear if the paradoxical effect is directly related to clusterin loss or is due to pleiotropic effects. Adding to this complexity, in the 5xFAD (familial Alzheimer’s disease) model mouse background, clusterin null mice showed fewer Abeta plaques and cognitive performance deficits compared to clusterin-expressing mice at 5 months of age, though the differences disappeared by 10 months, suggesting that clusterin expression is only required for early toxicity ( Oh et al, 2019 ).…”
Section: Clusterinmentioning
confidence: 99%
See 1 more Smart Citation